Predicting the broadband response of a layered cone-cylinder-cone shell - Chronopoulos, Dimitrios; Ichchou, Mohamed; Troclet, Bernard; Bareille, Olivier (Elsevier, 2014)
The dynamic response of an aerospace layered structure composed of a combination of conical and cylindrical shells is hereby modelled. In the low and the mid-frequency ranges a WFEM derived ESL approach implemented within a FEM is used in order to predict the response of the shell. Furthermore, in the high frequency range the CLF of the connected subsystems are calculated using a WFEM/FEM approach. These CLF are implemented within a SEA approach in order to predict the structural response. The accuracy and robustness of the developed approaches are exhibited by comparisons to experimental measurements on a layered conical-shell-conical configuration.